SURGICAL TREATMENT OF PURULENT-NECROTIC SOFT TISSUE COMPLICATIONS IN PATIENTS WITH DIABETES MELLITUS AND DIABETIC FOOT - Sayfulla Abdullaevich Abdullaev (Scholar Express Journals, 2023)
According to the literature, the incidence of diabetes mellitus has been increasing in recent years. In the developed countries of the world up to 5-6% of the population suffer from complications of diabetes mellitus. Complication with surgical infection in diabetes mellitus accounts for up to 30-40% of all surgical patients.
Keywords: diabetic foot; purulent-necrotic wounds; diabetes mellitus; fasciitis